A standardized approach to study human variability in isometric thermogenesis during low-intensity physical activity - Sarafian, Delphine; Miles, Jennifer L.; Yepuri, Gayathri; Montani, Jean-Pierre; Schutz, Yves; Dulloo, Abdul G. (Frontiers in Physiology, 2013)
Limitations of current methods: The assessment of human variability in various compartments of daily energy expenditure (EE) under standardized conditions is well defined at rest (as basal metabolic rate and thermic effect of feeding), and currently under validation for assessing the energy cost of low-intensity dynamic work. However, because physical activities of daily life consist of a combination of both dynamic and isometric work, there is also a need to develop standardized tests for assessing human variability in the energy cost of low-intensity isometric work. Experimental objectives: Development of an approach to study human variability in isometric thermogenesis by incorporating a protocol of intermittent leg press exercise of varying low-intensity isometric loads with measurements of EE by indirect calorimetry. Results: EE was measured in the seated position with the subject at rest or while intermittently pressing both legs against a press-platform at 5 low-intensity isometric loads (+5, +10, + 15, +20 and +25 kg force), each consisting of a succession of 8 cycles of press (30 s) and rest (30 s). EE, integrated over each 8-min period of the intermittent leg press exercise, was found to increase linearly across the 5 isometric loads with a correlation coefficient (r) > 0.9 for each individual. The slope of this EE-Load relationship, which provides the energy cost of this standardized isometric exercise expressed per kg force applied intermittently (30 s in every min), was found to show good repeatability when assessed in subjects who repeated the same experimental protocol on 3 separate days: its low intra-individual coefficient of variation (CV) of ~ 10% contrasted with its much higher inter-individual CV of 35%; the latter being mass-independent but partly explained by height. Conclusion: This standardized approach to study isometric thermogenesis opens up a new avenue for research in EE phenotyping and metabolic predisposition to obesity